2022
DOI: 10.7759/cureus.26824
|View full text |Cite
|
Sign up to set email alerts
|

Rechallenging Fluoropyrimidine-Induced Cardiotoxicity and Neurotoxicity: A Report of Two Cases

Abstract: Fluoropyrimidines (FP's) such as fluorouracil (5-FU) and capecitabine are antimetabolites widely used in many solid tumors. FPs side effects are caused mainly by a lack of dihydropyrimidine dehydrogenase (DPD) enzyme. It has been noticed that treatment with infusional regimens of 5-FU is associated with more adverse events (AE) compared to bolus forms. Here, we report two cases of unusual side effects seen with infusional 5-FU and capecitabine and how early intervention by withholding ongoing treatment can hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In the early and late stages of arteriosclerosis, a variety of procoagulants and antithrombin proteases are immunohistochemically labeled at different locations on the arteriosclerotic vessel wall, whereas the procoagulant state of early plaques are enhanced (55). An earlier single-center study of 1083 cancer patients who underwent 5-FU chemotherapy showed cardiotoxicity in 17 patients, angina in 15 patients, and definitive myocardial infarction in 1 patient (56). Another prospective clinical trial of 367 patients treated with high-dose 5-FU showed 28 cardiac events induced by 5-FU, with 18 patients experiencing angina at the beginning of treatment and 21 patients developing unstable angina after the withdrawal of 5-FU (57).…”
Section: -Fluorouracilmentioning
confidence: 99%
“…In the early and late stages of arteriosclerosis, a variety of procoagulants and antithrombin proteases are immunohistochemically labeled at different locations on the arteriosclerotic vessel wall, whereas the procoagulant state of early plaques are enhanced (55). An earlier single-center study of 1083 cancer patients who underwent 5-FU chemotherapy showed cardiotoxicity in 17 patients, angina in 15 patients, and definitive myocardial infarction in 1 patient (56). Another prospective clinical trial of 367 patients treated with high-dose 5-FU showed 28 cardiac events induced by 5-FU, with 18 patients experiencing angina at the beginning of treatment and 21 patients developing unstable angina after the withdrawal of 5-FU (57).…”
Section: -Fluorouracilmentioning
confidence: 99%